Identification and expression analysis of zebrafish gnaq in the hypothalamic–Pituitary–Gonadal axis - Wang, Chong; Yang, Le; Xiao, Tiaoyi; Li, Junhua; Liu, Qiaolin; Xiong, Shuting (Frontiers in Genetics, 2022)
The G proteins have emerged as essential molecular switches in a wide variety of signal transduction pathways. Gαq, encoded by G protein subunit alpha q (gnaq), is a member of the G proteins and participates in regulating important biological activities in mammals; however, its function and regulatory mechanism in teleost remain largely unclear. In the current study, we cloned the cDNA of gnaq from zebrafish (Danio rerio) and investigated the expression characteristics of Gαq/gnaq in reproductive tissues. RT-PCR and WISH analyses showed that gnaq was widely expressed in zebrafish tissues, with high expression in the brain, olfactory brain, and hypothalamus. During the embryonic development stage, the gnaq was mainly distributed in the hypothalamus after 72 h post-fertilization. In addition, immunohistochemistry analysis revealed that the Gαq protein was highly expressed in the diffuse nucleus of the inferior hypothalamic lobe (DIL), ventral zone of the periventricular hypothalamus (Hv), and caudal zone of the periventricular hypothalamus (Hc) in adult zebrafish. Furthermore, in the gonads, the Gαq protein was found in oocytes of all stages, except spermatids. Lastly, the gnaq mRNA exhibited relatively low expression in gonads on Day 4 during the reproductive cycle, while increasing drastically in the hypothalamus and pituitary afterward. Altogether, our results suggest that gnaq/Gαq might be important in fish reproduction.